A woman on the battlefield: Penthesilea in Ephemeris belli Troiani, by Dictis Cretense - Silva, Gelbart Souza [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2020)
In this article, we examine the characterization of Penthesilea in Ephemeris belli Troiani, an anonymous novel from the 4th century AD, regarding the tension between male and female genders. We intend to demonstrate that the narrator presents a moralizing approach and a characterization of the feminine gender as destructive and threatening and, in the case of Penthesilea, this threat becomes even greater because she enters a space limited to men: the battlefield. To that end, we compare Penthesilea and the representation of the female element in Ephemeris with other characterizations of the Amazons in the ancient tradition. We conclude that the Penthesileia's atrocious death described in the narrative is a punishment for her daring to occupy and exercise an exclusive male role.
Keywords: Ancient novel; Dictys Cretensis; Ephemeris belli Troiani; Penthesilea; Trojan War